Mengurus Wacana dan Kepimpinan: Analisis Ucapan Sulung Perdana Menteri Malaysia Keenam (Jurnal Bahasa, 2011)
This article analyses how Najib fulfilled his political needs in the speeches he made upon taking office as the Prime Minister of Malaysia on 3rd April 2009. The analysis emphasises how and why Najib managed his language during the early part of his tenure as the Prime Minister and, at the same time, how language functions in the process of leadership. As an analysis of discourse, focus is placed on discursive properties such as interpretation, production, generic structure, force of utterance distribution and usage; and textual features such as grammar, lexicalisation and theme. The article concludes that Najib's speeches as newly appointed leader were purposeful, well-timed, genuine and prepared with a view to helm the nation and that is the reason why they were well produced and well managed.Keywords: language, discourse analysis, leadership, discursive, textual, social life